Family-friendly policy in Central European countries - Zdulski, Mirosław (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
The aim of this paper is to describe the changes in the field of demography which took place after 1989 and their effects on families, as well as the policies implemented in the Czech Republic, Poland, Slovakia and Hungary in order to increase reproduction and the number of marriages.
Keywords: demographic change; pro-family policy; Central Europe